IDENTIFIKASI POTENSI PANTAI TOTOBANG SEBAGAI DAERAH WISATA DI PULAU MANADO TUA NEGERI - Julita Laluraga; Agustinus Walansendouw; Bet El S. Lagarense; Gerry Kadamehang (Jurnal Ilmu Pariwisata, 2022)
North Sulawesi has several interesting natural potentials to be developed. One of them is Totobang Beach located in Manado Tua Negeri, Bunaken Island. It can be reached in about one hour and thirty minutes from downtown Manado. The purpose of this study is to promote and identify Totobang beach as tourism attraction in the village of Manado Tua Negeri.This research uses qualitative methods called the naturalistic research method. This research was conducted in natural conditions and the researchers used data analysis techniques in the form of strategic environmental analysis, with several ndicators. The results of this study indicated that the identification of the potential of Totobang beach as a tourist area in the village of Manado Tua Negeri has currently needs soecial attentions . For this reason, cooperation from the local government, the manager and the local authority of Manado Tua Negeri village is needed in developing this Totobang Beach as tourist attraction. So that it will become a superior and best tourist destination with big influences on the number of tourist visit the village of Manado Tua Negeri.